Developments in the Turkish marine aquaculture sector - Deniz H.; Korkut A.Y.; Tekelioglu N. (Mediterranean offshore mariculture, 2000)
With significant resources in both the Black Sea and the Mediterranean, fisheries are an important element in the primary production sector of the Turkish economy. While major changes have occurred in capture fisheries, with a significant drop in production in the Black Sea, the marine aquaculture sector in Turkey is developing rapidly, with sea bass and sea bream farming the most important areas of growth, primarily in the south and west coastal regions. The large part of this development has been based on small farm units using simple inshore cage systems. However, the increasing move towards larger scale production is bringing about greater interest and investment in larger and more robust cage systems, sited in more open and exposed locations. This paper summarizes the current status of the industry and identifies trends towards offshore development.
Advanced Course of the CIHEAM Network on Technology of Aquaculture in the Mediterranean on 'Mediterranean Offshore Mariculture', 1997/10/20-24, Zaragoza (Spain)